Reflections on the process of selecting and preparing teams: the case of the brazilian youth masculine volleyball team - Viktor Shigunov; Milton Aparecido Anfilo (Universidade Federal de Santa Catarina, 2004)
This research was carried out with the aim to analyze the methodological strategy adopted by the coach of the Brazilian youth man volleyball team during training sessions in the preparation period. As a data gathering method, 45 videos were taken during sessions, 28 in Belo Horizonte and 17 in Poços de Caldas. A semi-structured interview was also held with the coach and the coaching staff . The results of the research indicated that the coach's pedagogical practice was strongly influenced by technical, developmental and systemic methodological conceptions. This practice was developed through a combination of different methodologies, such as analytic, synthetic, structuralist, dynamic and progressive. The relationship between the coaching staff and the athletes was harmonious and respectful. It was shown that, besides to anthropometric, conditioning, technical-coordinating, tactical-cognitive and psychological factors, the twelve athletes who represented Brazil in the World Youth Championshipwere also chosen for other qualities. Among the qualities to be mentioned are the capacity for leadership, group cohesion, courage and determination . The research pointed out that the preparation process of the Brazilian team was carried out with great competence, through a correct division of training time and a careful selection of the athletes, following international standard criteria such as height, strength and individual technical skills. RESUMO Esta pesquisa foi realizada com o propósito de analisar a estratégia metodológica adotada pelo técnico da seleção brasileira masculina de voleibol infanto-juvenil nos treinamentos no período preparatório da equipe. Como instrumento de coleta de dados, foram realizadas filmagens em vídeo de 45 sessões de treinamentos, sendo 28 em Belo horizonte e 17 em Poços de Caldas. Também foi realizada uma entrevista semi-estruturada com o treinador da seleção brasileira e a sua comissão técnica. Os resultados da pesquisa indicam que a prática pedagógica do técnico foi fortemente influenciada por concepções metodológicas tecnicistas, desenvolvimentistas e sistêmicas. A mesma foi desenvolvida através da combinação de diferentes metodologias, como as analíticas, sintéticas, estruturalistas, dinâmicas e progressivas. A relação da comissão técnica com os atletas foi harmoniosa e respeitosa. Verificou-se que além dos fatores antropométricos, condicionantes, técnico-coordenativos, tático-cognitivos e psicológicos, os doze atletas que representaram o Brasil no Campeonato Mundial da Juventude, também foram escolhidos por outras qualidades. Dentre essas qualidades, pode-se citar a capacidade de liderança, o espírito de equipe, a coragem e a determinação. A pesquisa apontou que o processo de preparação da seleção brasileira foi realizado com muita competência, através de uma periodização correta dos treinamentos e uma seleção criteriosa dos atletas, que seguiu padrões internacionais como a altura, força física e recursos técnicos individuais.